Anomalous bulk diffusion of methylene diphenyl diisocyanate in silicone elastomer. (October 2021) - Wortmann, Martin; Viertel, Klaus; Welle, Alexander; Keil, Waldemar; Frese, Natalie; Hachmann, Wiebke; Krieger, Philipp; Brikmann, Johannes; Schmidt, Claudia; Moritzer, Elmar; Hüsgen, Bruno
Highlights: MDI is absorbed by silicone, reacts with moisture to polyurea and forms clusters. Phase separation of polyurea and silicone causes time-dependent surface concentration. Polymerization of diffusing MDI causes time-dependent diffusion coefficient. Analytical solutions to diffusion equation are used to model concentration profile. Models are used to predict absorption measurements. Abstract: In this study, we investigate the anomalous diffusion of methylene diphenylmethane-4, 4′-diisocyanate (MDI) into fumed silica filled poly(dimethylsiloxane) (PDMS) elastomer, which occurs in the industrial application of polyurethane vacuum casting. The absorbed MDI polymerizes with moisture to polyurea within the silicone medium, forming a sequential semi interpenetrating polymer network. This results in the formation of polyurea clusters near the exposed surface. Here we focus on the spatially resolved chemical characterization on the micrometer scale utilizing time-of-flight secondary ion mass spectrometry (ToF-SIMS), transmission electron microscopy (TEM), helium ion microscopy (HIM), atomic force microscopy (AFM), thermo-gravimetric analysis (TGA), X-ray photoelectron spectroscopy (XPS) as well as nuclear magnetic resonance spectroscopy (NMR). The concentration profile was determined experimentally using a customized method based on TGA. It was shown that the polyurea reaction of the MDI causes a time-dependency of both the surface concentration and the diffusion coefficient. Six analytical solutions to the diffusion equation obeying different time-dependent boundary conditions with different physical implications are proposed and used to model the measured concentration profiles. The parameterized models showed good predictive power for the measured absorption data and thus substantiated the conjectured molecular phenomena. Graphical abstract: Image, graphical abstract